A Unique Topoisomerase II Inhibitor with Dose-Affected Anticancer Mechanisms and Less Cardiotoxicity - Zhi-Ying Li (MDPI AG, 2021)
Type II DNA topoisomerase (topo II) is an essential nuclear enzyme and a well-validated anticancer drug target. Previously, we have carried out several rounds of structural optimizations on our in-house topo II inhibitor E17, which was shown to have superior anticancer activity and less risk of multidrug resistance (MDR). Among the newly developed acridone derivatives, 6h displayed significant anticancer efficacy with unique mechanisms of action. At low concentrations, it arrested cancer cell cycles and triggered cell apoptosis, which is similar to the action of the well-known topo II inhibitor VP16. By contrast, 6h showed significant and long-term anti-proliferative activity at relatively high concentrations, with negligible influence on apoptosis. In addition, 6h exhibited no serious cardiotoxicity compared to doxorubicin (DOXO), a widely used topo II-targeting antineoplastic drug in clinic, but with damaging myocardial side effects. Collectively, our present work has supported the therapeutic value of 6h as a promising chemotherapy for cancers.